(untitled) (ENTHYMEMA, 2011)
The last few years have seen an increase in the publication of dictionaries for learners of Spanish as a foreign language. In this article we offer the analysis of one of the lexicographic products – which is pioneering in the field –, 1996’s Diccionario de Salamanca. With this analysis we aim to show some guidelines about the criteria that can help us in evaluating the quality of such a work. The main issue that we will need to consider is to what extent should such a type of product be different to products for native speakers. We will therefore compare it to two representative volumes in the field of ELE’s lexicography: the one by the Real Academia (DRAE)and the Diccionario del Español Actual (DEA), which is nowadays considered one of best in the market. We will therefore reflect on the elements that are useful and necessary in the field dedicate to this type of consumers.